Evaluating the effect of bilateral transcutaneous auricular vagus nerve stimulation on motor function recovery after stroke: A multicenter, randomized controlled trial protocol - Jia Wang; Xiaoyang Dong (PLoS ONE, 2026)
Introduction Previous studies have demonstrated that vagus nerve stimulation (VNS) is an emerging approach for stroke rehabilitation and numerous studies have shown that VNS can promote motor function recovery and alleviate neurological deficits both in clinical and animal models. However, current clinical applications primarily involve invasive or unilateral stimulation with limited sample sizes and a focus mainly on upper limb function. Recent evidence indicates that bilateral transcutaneous auricular vagus nerve stimulation (BtaVNS) may offer superior signal conduction and therapeutic outcomes compared with unilateral left transcutaneous auricular vagus nerve stimulation (LtaVNS). To date, the efficacy and safety of BtaVNS for comprehensive limb motor rehabilitation after stroke remain underexplored. This study aims to address this gap by conducting a multicenter, randomized controlled trial evaluating BtaVNS in post-stroke patients with hemiplegic limb motor dysfunction. Methods and analysis We will conduct a prospective, double-blind, multicenter randomized controlled trial involving 114 stroke patients diagnosed with hemiplegic limb motor dysfunction. Participants will be randomly assigned to one of three groups: a BtaVNS group, a LtaVNS group, or a control group. All groups will receive routine post-stroke rehabilitative therapy, while the intervention groups will additionally receive non-invasive taVNS: either bilaterally or on the left ear only. The taVNS parameters will be set at 20 Hz frequency, 300 µs pulse width, and individually adjusted intensity (0.5-1 mA), delivered for 30 minutes per session, twice daily, six days per week for four weeks. The co-primary outcomes include the Fugl-Meyer Assessment of Upper Extremity (FMA-UE) and Fugl-Meyer Assessment of Lower Extremity (FMA-LE). Secondary outcomes include the Wolf Motor Function Test (WMFT), Berg Balance Scale (BBS) and Modified Barthel Index (MBI). Exploratory outcomes include neuroimaging evaluations using functional near-infrared spectroscopy (fNIRS). Assessments will be conducted at baseline, after 2 weeks of treatment, after 4 weeks of treatment and at the 8-week follow-up. Safety and adverse events will be monitored throughout the study. Trial registration number ChiCTR2400093825